Implementasi Model Pembelajaran Guided Discovery Learning Untuk Meningkatkan Berpikir Kritis Siswa - Sari Dianti; Dini Meldiya Putri; Liza Nopita Sari; Elvi Yulianti Yulianti; Andrian Topano (UMSU, 2023)
Critical thinking is a systematic and active cognitive process in assessing arguments, assessing a fact, assessing the richness and relationship of two or more objects and providing evidence to accept or reject a statement. This ability can be improved through the guided discovery learning model which prioritizes student activity during the learning process so that they can formulate their own information obtained scientifically. So the purpose of this study is to find out how to implement the guided discovery learning model in an effort to improve students' abilities in terms of critical thinking. This research uses a quantitative approach using a quasi-experimental method with a factorial design model. The treatment variable is the guided discovery learning method, the dependent variable is the level of critical thinking and motivation as the moderator variable. Based on the results of this study, the implementation of the guided discovery learning method is able to improve students' critical thinking. this is evidenced by the probability value of 0.00 α = 0.05, Ho, and sig 0.002 α = 0.05, Ho means that there are differences in the level of students' critical thinking between classes using guided discovery learning methods and classes using conventional methods.